2021
DOI: 10.1177/10497315211003322
|View full text |Cite
|
Sign up to set email alerts
|

Black Youth and African-Centered Interventions: A Systematic Review

Abstract: Purpose: This review discusses the effectiveness of African-centered interventions (ACIs) with Black youth. Methods: The authors conducted a comprehensive search of ACIs using electronic bibliographic databases to identify studies completed in the United States and reported in peer-reviewed journals. A total of 10 studies were identified that met the full inclusion criteria of the review. Results: Collectively, we found that ACIs are associated with positive outcomes in Black youths’ academic achievement, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…As such, Ubuntu appears to provide an excellent framework for psychotherapy and other interventions for Black Americans. Prior research also shows that African-centered interventions are particularly effective for Black youth with respect to academic achievement, self-image, and behavior (Lateef et al, 2022). Combined with the current results, this culminates in a tripartite model for Ubuntu and mental health, where Ubuntu is positively associated with mental health, seeking support for mental health problems, and the results that can be obtained from interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As such, Ubuntu appears to provide an excellent framework for psychotherapy and other interventions for Black Americans. Prior research also shows that African-centered interventions are particularly effective for Black youth with respect to academic achievement, self-image, and behavior (Lateef et al, 2022). Combined with the current results, this culminates in a tripartite model for Ubuntu and mental health, where Ubuntu is positively associated with mental health, seeking support for mental health problems, and the results that can be obtained from interventions.…”
Section: Discussionmentioning
confidence: 99%
“…They posit that critical components include several common to the STB prevention literature, such as the improvement of interpersonal interactions, coping, and self-esteem. A recent systematic review found promising evidence for the effectiveness of culturally affirming African-centered interventions on Black youth self-concept, behaviors, cultural identity, and academic achievement (Lateef et al, 2022 ). However, similar to a review on culturally sensitive interventions for Native American youth (Jackson & Hodge, 2010 ), the authors concluded that additional, more rigorous research is needed to measure the extent to which such approaches improve different aspects of youth wellbeing.…”
Section: Common Types Of School-based Programs With Promise For Cross...mentioning
confidence: 99%
“…The assessment of study quality and rigor standards are based on a rating benchmark drawn from the American Psychological Association on assessing interventions [9]. These include six standards: (a) randomization of sample, (b) comparison with other treatments or standard services, (c) definition of a specific problem or population, (d) use of validated and reliable outcome measures, (e) use of treatment manuals or curriculum, and (f) large sample size (i.e., more than 25 per group) [9](p. 4).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…A point was given for each standard. Higher scores indicate a higher level of methodological rigor[9] (p. 4).…”
mentioning
confidence: 99%